A Perspective of Coagulation Dysfunction in Multiple Sclerosis and in Experimental Allergic Encephalomyelitis - Plantone, Domenico; Inglese, Matilde; Salvetti, Marco; Koudriavtseva, Tatiana (Frontiers in Neurology, 2019)
In multiple sclerosis (MS), a key role of both coagulation and vascular thrombosis has been reported since the first descriptions of the disease. Subsequently, the observation of a close concordance between perivascular fibrin(ogen) deposition and the occurrence of clinical signs in experimental allergic encephalitis (EAE), an animal model of MS, led to numerous studies to investigate the role of thrombin and fibrin(ogen). Most findings supported that both human and animal disease exacerbation is a condition characterized by an increased coagulation activity. Indeed, the activation of microglia, resident innate immune cells, occurs early after fibrinogen leakage already in pre-demyelinating lesion stage in EAE and MS. Finally, it has been proven that the use of several anticoagulant agents can successfully improve EAE. Altogether, these studies highlight the role of the coagulation pathway in the pathophysiology of MS and suggest possible therapeutic targets that may complement existing treatments.